Assessing what generates precompetitive emotions: development of the precompetitive appraisal measure - Wolf, S. A.; Evans, B.; Laborde, S.; Kleinert, J. (Journal of Sports Sciences, 2015)
Athletes` precompetitive appraisal determines which emotion they experience with regard to an upcoming competition. Such precompetitive emotions have powerful and potentially destructive consequences for performance. To control and optimise these consequences, it is important to examine precompetitive appraisal. Currently, such efforts are hampered by the lack of a valid measurement tool. The present study aimed to develop a novel measure of precompetitive appraisal. Specifically, the Precompetitive Appraisal Measure (PAM) was constructed by adapting an existing self-report scale. Female and male intercollegiate team sport athletes (N = 384) completed the PAM, along with a measure of intensity and interpretation of precompetitive anxiety symptoms (CSAI-2D) prior to competition. On these responses, (a) a Principal Component Analysis and a Confirmatory Factor Analysis supported the PAM`s suggested two-factor structure (Primary and Secondary Appraisal), (b) cluster analyses indicated the measure`s ability to distinguish theoretically congruent appraisal profiles (Threat and Challenge) and (c) a MANOVA and multiple regression analyses demonstrated that PAM-responses predicted precompetitive symptom intensity and interpretation. Further, analyses revealed that the majority of athletes appraised the upcoming competition as a challenge.